The Stylistic of Titling In the collection of stories "Alsaketa" to Haifa Bitart - Abu Adal, Mohammed Ahmed (Journal of Humanities & Social Sciences, 2018)
This research studied "label in a “Assaketa" to Haifa Bitar, hoping in a statement ways of expression adopted by narrator in her titles; to discover her focus on two techniques that irony and paradox; therefore initiated in the Brief definition of the irony concept with different types, then move on to the statement processes of her harnessed to servicing method, and significance for which it was used to from the stylistic approaches and inductive. At the bilateral level speech and language, statement was ironic effect in the stylistic changes are reflected on the evolution of meaning, apart from two meanings the Postural and emergency of the title, irony comes; to produce the third signified which represents the counter meaning to what the illusion of speech. With regard to the paradox has been first raised confusion existing between it and the irony, then move on to a statement of the use of irony, which focused on monitoring dissonance is uncommon in the Additional compositions, and the board narrative of major impact in the detection of surprisingly so jarring employee to lure the reader and rhythm to it. In both signifier and the signified, search explained semantic richness of some narrative titles with (Bitar), but it is available richness to many possibilities, can be identified only in the light of the text of the story. Finally, contemplates search types singularity and privacy addresses stories as internal addresses of the group "Fallen", and internal addresses of the novel generally according Stylistics Comparative determine characterized addresses Alsardh for others, such as focusing on topics sad, embodies Alsardh through qualities such as:(injustice, immorality, abandonment, betrayal, oppression, tyranny, inferiority, oppression, poverty, etc.).